Tuberculosis of the distal ulna mimicking malignanacy - a rare case report - Sudhir Shyam Kushwaha; Kumar Shantanu; Deepak Kumar; Shailendra Singh; Vineet Sharma (International Journal of Medical Research and Review, 2016)
The tubercular involvement of the long bones of the extremities is very rare so, tuberculosis as a differential diagnosis is usually missed when a patient present with pain and swelling over long bones. The radiology is usually suggestive of the malignancy. We hereby present a case with pain and swelling over the ulna with a suspicion of malignanacy, but biopsy and per-operative findings were suggestive of tuberculosis.